Pengaruh Self Expressive Brand Terhadap Brand Accaptance Melalui Word Of Mouth - Muliani Marwah Sismy; Aulia Arief Nasution; Indra Syafii (Inovatif: Jurnal Ekonomi, Manajemen, Akuntansi, Bisnis Digital dan Kewirausahaan, 2022)
The purpose of this study was to examine and analyze the effect of self-expressive brand on brand acceptance through word of mouth. In the people of Medan City who buy H&M products directly or indirectly. The approach used in this study is a causal approach. The population in this study were all the people of Medan City who bought H&M products. The sample in this study used quota sampling totaling 100 people in Medan City who bought H&M products. Data collection techniques in this study used documentation, observation, and questionnaire techniques. The data analysis technique in this study used a quantitative approach using statistical analysis using the Auter Model Analysis test, Inner Model Analysis, and Hypothesis Testing. Data processing in this study using the PLS (Partial Least Square) software program. The results of this study prove that directly self-expressive brands and word of mouth affect brand acceptance, self-expressive brands affect word of mouth, the results of this study indirectly state that self-expressive brands affect brand acceptance through word of mouth.